2001
DOI: 10.1007/bf02703405
|View full text |Cite
|
Sign up to set email alerts
|

Surface waves in fibre-reinforced anisotropic elastic media

Abstract: The aim of this paper is to investigate surface waves in anisotropic fibre-reinforced solid elastic media. First, the theory of general surface waves has been derived and applied to study the particular cases of surface waves -Rayleigh, Love and Stoneley types. The wave velocity equations are found to be in agreement with the corresponding classical result when the anisotropic elastic parameters tends to zero. It is important to note that the Rayleigh type of wave velocity in the fibre-reinforced elastic mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(63 citation statements)
references
References 8 publications
2
60
0
Order By: Relevance
“…For k = 0 and by ignoring the voids and gravitational effects our results are same as that of Sengupta and Nath (2001). If one ignores the fibrereinforced parameters also then results are same as Rayleigh (1885).…”
supporting
confidence: 63%
See 2 more Smart Citations
“…For k = 0 and by ignoring the voids and gravitational effects our results are same as that of Sengupta and Nath (2001). If one ignores the fibrereinforced parameters also then results are same as Rayleigh (1885).…”
supporting
confidence: 63%
“…Study of the phenomenon of rgravity field is also used to improve the conditions of oil extractions. Finally, if the rotation is neglected, the relevant results obtained are deduced to the results obtained by Sengupta and Nath (2001).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Sengupta and Nath [2] discussed the problem of surface waves in fibre-reinforced anisotropic elastic media. Singh [3] showed that, for wave propagation in fibre--reinforced anisotropic media, this decoupling cannot be achieved by the introduction of displacement potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Chattopadhyay and Choudhury [1995] studied magnetoelastic shear waves in an infinite self-reinforced elastic plate. Sengupta and Nath [2001] investigated surface waves (Rayleigh, Love and Stoneley types) in anisotropic fiber-reinforced solid elastic media. Pradhan et al [2003] studied the dispersion of Love waves in a self-reinforced layer over an elastic non-homogeneous half-space.…”
Section: Introductionmentioning
confidence: 99%